Konvergensi Bank dan Ketahanan Bank terhadap Pandemi - Pandu Adi Cakranegara, (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2024)
Book bank 4 is the bank with the largest number of assets and controls more than half of the banking market in Indonesia. Since the early 2000s BUKU 4 bank is an exclusive club consisting of the 4 largest banks in Indonesia. This changed in 2017 when CIMB Niaga bank entered BUKU 4 bank and a year later Panin bank joined. This study examines what factors underlie these banks can merge into a BUKU 4 bank. Further this research then examines the resilience of BUKU 4 banks to the pandemic. The research method is a quantitative method using multiple linear regression. The research uses data taken from the financial statements of 2010 to 2018. The results show that the factors that drive the convergence of banks are the factors of capital adequacy, low borrowing loans and operational efficiency of banking. Meanwhile, in order for banks to survive this research finds investment factors in technology, maintaining capital adequacy and unpaid debt management.